Economic burden and financial vulnerability of injuries among the elderly in Vietnam - Hai Minh Vu; Linh Gia Vu; Tung Hoang Tran; Laurent Boyer; Pascal Auquier; Guillaume Fond; Tham Thi Nguyen; Linh Khanh Le; Hoa Thi Do; Huyen Phuc Do; Son Nghiem; Carl A. Latkin; et al. (Scientific Reports, 2023)
Abstract Falls are a leading cause of death among elderly people. However, research on the cost of fall-related injuries is limited in Vietnam. We estimated treatment costs and associated factors among 405 elderly patients in Thai Binh hospitals. Costs were estimated through self-reported data on medical and non-medical expenses. Logistic regression and GLM were used to identify payment and affordability factors. Inpatient and outpatient care costs for fall-related injuries were US$98.06 and US$8.53, respectively. 11.85% of participants couldn’t pay for treatment. Payment ability and cost decline were linked to family income, medical history, and hospital stay length. Elderly with fall-related injuries in Vietnam experienced high costs and severe health issues. Primary healthcare services and communication campaigns should be strengthened to reduce disease burden and develop effective fall injury prevention strategies.